The Effect of Cow Manure and Cow Dung Biochar Application on P Available and Growth of Corn Plants in Ultisol - Lumbantobing, Romauli; Hidayat, Benny; Lubis, Alida (Jurnal Online Pertanian Tropik, 2020)
Cow manure and cow dung biochar have great potential in increasing P available in Ultisol soil. The application of cow manure and cow dung biochar on P available and the growth of corn plants in Ultisol soil was done to compare the effect between the two treatments. This research used a non-factorial randomized block design with 7 treatments, namely: control, 3 levels of cow manure with a dose of 5, 10, and 15 tons/ha, and 3 levels of cow dung biochar with a dose of 5, 10, 15 tons/ha and 4 blocks. The parameters measured were H2O pH, P available, P total, Al-dd, C organic, plant height, canopy dry weight, and plant P uptake. The research results showed that the application of cow manure and cow dung biochar was able to increase H2O pH, P available, P total, C organic, plant height, canopy dry weight, plant P uptake, and was able to reduce the Al-dd in Ultisol soil. Cow dung biochar was better in increasing H2O pH, P available and P total of Ultisol compared to cow manure.